2021
DOI: 10.3390/electronics10111250
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Cognitive Assistants for Attitude and Behavior Change Support in Mental Health: State-of-the-Art Technical Review

Abstract: Intelligent cognitive assistant (ICA) technology is used in various domains to emulate human behavior expressed through synchronous communication, especially written conversation. Due to their ability to use individually tailored natural language, they present a powerful vessel to support attitude and behavior change. Behavior change support systems are emerging as a crucial tool in digital mental health services, and ICAs exceed in effective support, especially for stress, anxiety and depression (SAD), where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 89 publications
1
11
0
Order By: Relevance
“…In particular, ICA can effectively support stress, anxiety, and depression (SAD) by analyzing people's emotional and cognitive phenomena. 14 Depression is the most frequent in psychiatric disorder studied via mobile devices. It affects more than 300 million people worldwide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, ICA can effectively support stress, anxiety, and depression (SAD) by analyzing people's emotional and cognitive phenomena. 14 Depression is the most frequent in psychiatric disorder studied via mobile devices. It affects more than 300 million people worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ICA can effectively support stress, anxiety, and depression (SAD) by analyzing people’s emotional and cognitive phenomena. 14 …”
Section: Introductionmentioning
confidence: 99%
“…Conversational intelligent agents have been extensively researched and applied in many fields, including health care [24], finance [25], environmental sciences [26], psychology [27], and administration [28]. They have required the development of taxonomy, natural-language processing approaches, interaction methods and interfaces, and intent mapping (e.g., scoring), and are often developed for specific use cases by an experienced developer team.…”
Section: Relevant Workmentioning
confidence: 99%
“…In this sense, several studies were also observed using either physical or virtual robots or assistants to directly interact with the elderly person and attempt to persuade him/her to be healthier [8,[17][18][19][20][21][22]. In fact, the authors in [23] explained the importance of intelligent cognitive assistants to support attitude and behavior changes, which are crucial to protect against the deterioration of cognitive and mental health. Furthermore, other authors explain the importance of building a relationship with a virtual entity, and why this approach could be meaningful for the elderly person, promoting feelings of responsibility and even nostalgia as they to look after another person/being [24][25][26].…”
Section: Introductionmentioning
confidence: 99%